Estudo da suscetibilidade de amastigotas extracelulares das cepas G e CL de Trypanosoma cruzi a componentes do sistema imune inato e adaptativo. Avaliação da atividade pró-fagocítica da P21-His6 - Rodrigues, Adele Aud (2011)
Trypanosoma cruzi is the ethiologic agent of Human Chagas disease. Due to T. cruzi wide genetic diversity, the species has been divided in six Discrete Typing Units (DTU), named T. cruzi I to VI. The G strain belongs to T. cruzi I group and CL to T. cruzi VI. Extracellular amastigotes forms (EA) are considered important in maintaining the vertebrate host cycle. Studies concerning the difference of infectiveness and the characterization of immunologic susceptibility in parasites belonging to different groups are relevant so that therapies based upon immunological response may be efficient for all distinct phylogenetic groups. T. cruzi´s P21 protein has recently been characterized and its probable action in parasites internalization process into host cell was observed. To give continuity to the functional characterization of T. cruzi´s P21 employing its recombinant form (P21-His6) is of great relevance taking into account that these could in the future take part into the potential therapeutic goals. This work intended to compare the in vivo and in vitro infection of EA from G and CL strains, as well as to assess P21-His6pro-phagocytic potential. So that experiments in vitro and in vivo have been made. in vitro assays showed a greater infectiveness and multiplication of EA from G strain than of CL. Nevertheless EA from G strain showed more susceptible as to inflammatory macrophages action in ex vivo experiments as to those differenciated and in vitro stimulated with IFN-γ. Among the G strain infected animals, only Calomys callosus showed sub-patent parasitemia and the IL-12 and IFN-γ knockouts showed patent parasitemia and high mortality. All the CL strain infected animals showed parasitemia, but the TNF-α, iNOS, Myd-88 and IL-12 knockouts showed greater parasitemia and mortality in comparision to the wild ones. In the assays of immunossupressed mice, it has been observed high parasitemia for CL and G strains. We, then conclude that EA from G strain probably don t show in vivo parasitemia due to its greater susceptibility to IFN-γ activated macrophages. To study P21 protein it has been made in vitro invasion and phagocytosis assayes in that C. callosus peritoneal macrophages were infected with T. cruzi´s EA, Leishmania amazonensis promastigotes, Toxoplasma gondii taquizoitas or otherwise invadid with zymozan particle, and then treated or not with P21-His6. It has also been made immunofluorescence of actin filaments in macrophages treated or not with P21-His6. Finaly, another immunofluorescence reaction was made in order to mark actin filaments in macrophage submitted to P21-His6, to wortmanin treatment, or both. Results showed that P21-His6 hightened all parasites and the inactive particle internalization. Besides macrophages treated with the protein showed increase in cortical actin polymerization. Nevertheless, the treatment with wortmanin together with P21-His6 inhibited its action in actin cellular polymerization. We conclude that P21-His6 is capable of inducing inespecific phagocytic process probably to its action into the cortical actin cytoskeletal, by means of signalization process probably depending on PI3-kinase activation.